Supra-normal values in resuscitation (Colombia Medica, 1994)
Resuscitation in severe traumatic hemorrhagic shock, septic patients, and products of major surgery must reach supranormal values within the first 12 hours after the injury event. lf this goal is accomplished, oxygen debt (resulting from the shock period and flow redistribution) will be rapidly paid. If it is not, organ dysfunction and mortality shall considerably increase. Traditional resuscitation has always looked to reestablish vital signs to normal values as soon as possible. On the other hand, aggressive resuscitation aims to obtain earlier and lofty supra-normal values related to circulatory parameters, oxygen transportation, and consumption, as well as pay the oxygen debt and reduce metabolic acidemia. These differences between both approaches are evaluated, and their results are shown in the present paper.